DEVELOPMENT OF 3D WALL MAGAZINE LEARNING MEDIA TO IMPROVE STUDENTS' COGNITIVE UNDERSTANDING OF THE MATERIAL ON THE HISTORY OF THE NATIONAL MOVEMENT FOR CLASS XI SMAN 1 LIRIK: Pengembangan Media Pembelajaran Mading 3D Untuk Meningkatkan Pemahaman Kognitif Siswa Pada Materi Sejarah Pergerakan Nasional Kelas XI SMAN 1 Lirik - Mirza Dwi Sukma Eca; Ahmal; Refli Surya Barkara (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research is a type of Research and Development (R&D) that aims to develop 3D Wall Magazine media to improve students' cognitive understanding of national movement history material in class XI SMA N 1 Lirik. The development model used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study consisted of 7 students for the small group trial and 18 students from class XI.3 SMA N 1 Lirik for the large group trial. Data collection instruments included observation, interviews, tests (pretest-posttest), and questionnaires. Data analysis used qualitative and quantitative analysis, including calculations of feasibility percentages and N-gain Scores for media effectiveness.The results showed that the 3D Wall Magazine media is